The Plant Wisdom of Dayak Ot Danum, Central Kalimantan - Herianto Herianto; Zaenal Kusuma; Ellis Nihayati; Cahyo Prayogo (Journal of Tropical Life Science, 2018)
This research aims to describe plants diversity having local wisdom value for Ot-Danum Dayak people, Tumbang Payang village and Tumbang Kania village, Central Kalimantan. The result reveals that since a long time ago, Ot-Danum Dayak people truly depend on natural resources to meet various daily needs. The vast majority of subsistence and society's income are form forest plants product. Plant diversity can provide food product for society, can produce various plants to be consumed and also produce alternative income sources, such as exploited for food, medicine, fermentation, tonic, cosmetic, building material and etc. However, the existing plant diversity is endangered since deforestation and forest degradation, and even there are many lesser-known species. Therefore, it needs to quickly find the information about the species to conservation effort, given the existing forest resource has a big potential to be developed and cultured to the species through domestication and providing a genetic resource for hybridization and selection.